2012
DOI: 10.1680/geot.10.p.037
|View full text |Cite
|
Sign up to set email alerts
|

Gold tailings liquefaction under critical state soil mechanics

Abstract: The results from a laboratory testing programme designed to evaluate the behaviour of gold tailings are presented, and interpreted in the critical state framework. Drained and undrained triaxial tests sheared under monotonic loading allowed the critical state line (CSL) to be established. The observed highly non-linear shape of the CSL was used to investigate the intrinsic dynamics of the monotonic undrained response of tailings, and to define the undrained instability state. This behaviour is useful in explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 12 publications
5
33
0
1
Order By: Relevance
“…Been et al (1991) reported the existence of a bilinear critical state line (CSL) for drained and undrained shearing of sands, and Yamamuro and Lade (1996) showed that the sharp change in slope in the CSL observed was associated with a larger incidence of particle breakage. Similar observations were also reported by Bedin et al (2012) for mine tailings. In addition, Russell and Khalili (2004) identified a third linear segment of the CSL in which compression was the governing deformation mechanism.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Been et al (1991) reported the existence of a bilinear critical state line (CSL) for drained and undrained shearing of sands, and Yamamuro and Lade (1996) showed that the sharp change in slope in the CSL observed was associated with a larger incidence of particle breakage. Similar observations were also reported by Bedin et al (2012) for mine tailings. In addition, Russell and Khalili (2004) identified a third linear segment of the CSL in which compression was the governing deformation mechanism.…”
Section: Introductionsupporting
confidence: 91%
“…In addition, while a single transition in slope in the CSL of other granular materials has been attributed to particle breakage or crushing from a qualitative standpoint, i.e. gold tailings at ′ = 225 (Bedin et al, 2012) and cambria sand at ′ = 4 (Yamamuro and Lade, 1996), only limited studies have demonstrated quantitatively the effects of breakage. Another aspect illustrated in Fig.…”
Section: Stress-strain Behaviour and Associated Breakagementioning
confidence: 99%
“…Russell and Khalili (2004) described the behaviour of crushable granular materials using a three-segment CSL within a boundary surface constitutive model. Bedin et al (2012) through a series monotonic triaxial testing on gold tailings observed a highly non-linear shape of CSL and stated that the curvature was due to particle breakage. Daouadji et al (2001) represented the position of the CSL in terms of the amount of energy needed for grain breakage, showing that the CSL in the e-lnp' domain descends according to the evolution of particle gradation.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of atmospheric rainfall on the dam seepage is obvious, the heavier the rainfall, the higher the infiltration line, the more disadvantageous to the dam stability [9]. Tailings are non-sticky or less viscous bulk soils, which are easily led to be liquefied [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%